Surface oxide analysis of water atomised Al and Al-Si powders - Hertl, Bojan (Kovine zlitine tehnologije, 1995)
A water atomisation technique has been used to produce rapidly solidified Al and Al-Si powders. The thickness of the oxide layer was determined by Auger electron spectroskopy (AES). The type of the oxide was determined by x-ray diffraction.
Keywords: vodna atomizacija; oksidne plasti